2006
DOI: 10.1002/j.1681-4835.2006.tb00186.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐Commerce Diffusion in Small Island Countries: The Influence of Institutions in Barbados

Abstract: This paper concerns the role of institutions in promoting the diffusion of e-commerce. Using institutional theory as a framework of analysis, the paper evaluates institutional interventions over a six-year period in Barbados and how that impacted on the national environment for ecommerce. The paper explicates the institutional powers of influence and regulation in the context of the ideologies of market supply and demand for e-commerce. It concludes that at the early stage of e-commerce diffusion both public a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The findings from this study show that besides innovation factors other factors such as environment (competitive pressure) and management (relative advantage) are also important to help understand the adoption of e-commerce in South Africa. Molla et al (2006) argued that in developing countries successful adoption of e-commerce strategy depends on the perceived e-readiness in e-commerce, managerial, organisational and environmental contexts. Researchers need to keep this in mind when considering any study on factors influencing the adoption of an innovation (Looi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The findings from this study show that besides innovation factors other factors such as environment (competitive pressure) and management (relative advantage) are also important to help understand the adoption of e-commerce in South Africa. Molla et al (2006) argued that in developing countries successful adoption of e-commerce strategy depends on the perceived e-readiness in e-commerce, managerial, organisational and environmental contexts. Researchers need to keep this in mind when considering any study on factors influencing the adoption of an innovation (Looi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…(2000) identify differences in language and work habits as one of the barriers to people using ECommerce. The majority of the content of the World Wide Web is produced in the English language, creating a barrier for many potential users in LDCs, especially those in African states whose first and second languages are not English (Molla et al, 2006). Molony (2008) found that despite the huge uptake of ICT-related technologies such as mobile phones in particular, some traditional pre-ICT aspects of the African business culture are set to remain for some time.…”
Section: Perceived Environmental Ereadinessmentioning
confidence: 99%
“…Without competitive offerings, even the near geographical proximity of North America will continue to work against firms in the region. Thus the imagery envisaged of burgeoning global commodity supply chains of e-commerce for these states seems illusory because of their firms' high start-up costs, the factor conditions, product selection, and the institutional norms of behavior of firms that significantly reduce their ability to compete at a global scale and expand their market reach (Allen Consulting Group, 2003;ECLAC, 2013;Fraser & Vuylsteke, 2011;Molla et al, 2006, p. 3; see also, Wresch & Fraser, 2005) while further increasing the dominance by firms of developed countries. Regardless of appropriately written regulations and well-designed infrastructure, this harsh reality reinforces a healthy skepticism about the relevance of e-commerce and its benefits to developing countries (Straub, 2003).…”
Section: Where's the Reciprocity When Asymmetries Of Trade Exist?mentioning
confidence: 98%
“…the charges operators pay for using another operator's wire network to complete calls (Allen Consulting Group, 2003, p. 31;UNCTAD, 2015). While e-commerce diffusion is not totally dependent on the cost of telecommunications, local businesses, and consumers lament the exorbitant fees charged for broadband connections, which make it unfeasible to establish a viable e-commerce presence (McClean, 2004in Molla et al, 2006; see also Barbados Advocate, 2012, 2014b. A reasonable discussion on e-commerce must therefore [re]image some of its analysis of how technological connectivity is constantly changing and how ICTs are being used by individuals from different backgrounds.…”
Section: Limitations and Asymmetries Of Infrastructurementioning
confidence: 98%